NEUROLOGICAL MANIFESTATIONS OF INFLUENZA INFECTION IN ADULTS AND CHILDREN: RESULTS OF A NATIONAL BRITISH SURVEILLANCE STUDY. Issue 11 (9th October 2013) - Goenka, Anu; Michael, Benedict; Ledger, Elizabeth; Hart, Ian; Absoud, Michael; Chow, Gabriel; Lilleker, James; Lim, Ming; Lunn, Michael; Peake, Deirdre; Pysden, Karen; Roberts, Mark; et al.
Abstract : Introduction: In recent years an increasing range of neurological syndromes has been associated with the emergence of novel influenza A:H1N1 (2009), and other influenza viruses. We aimed to describe the features of adults and children with neurological manifestations associated with influenza in the UK. Method: A surveillance study was performed in conjunction with the BNSU and BPNSU* over a 24–month period (February 2011 to February 2013). Inclusion criteria specified acute neurological illness within 1 month of proven influenza infection and prospective case definitions were applied. Results: Twenty–five cases were identified: 4 adults and 21 children [6 (23%) with pre–existing neurological disorders]. Four (16%) cases (all with encephalopathy syndromes) died. Twenty cases (80%) required admission to intensive care. Seventeen (68%) had Glasgow Outcome Scores of 2–5 indicating poor outcome. Polymerase chain reaction (PCR) of respiratory secretions identified: influenza A in 21 (20 H1N1) and influenza B in 4 cases. Two had co–infection with Streptococcus pneumoniae (one adult with septicaemia; one child with meningitis). Cerebrospinal fluid (CSF) revealed a pleocytosis in 3 out of 18 cases (median 184×106 cells/litre [range 16–900]). Influenza PCR was negative in all 10 CSF samples tested. Cerebral magnetic resonance imaging was performed in 3 cases, computerised tomography in 6, and 14 had both. Recognised acute encephalopathy syndromes were seen in 5, and non–specific changes including cerebral oedema and/or diffusion restriction in 5. For the 4 adults, 2 presented with acute extrapyramidal movement disorders, 1 with Guillain–Barré syndrome and 1 with acute encephalopathy. Of the 21 children, 17 presented with acute encephalopathy, 3 with encephalitis and 1 with acute dyskinesia. Encephalopathy syndromes were documented in 7 cases (6 children, 1 adult). They were characterised by their clinical presentation and neuroimaging and included 4 with Acute Necrotising Encephalopathy (ANE), 1 Acute Infantile Encephalopathy Predominantly Affecting the Frontal Lobes (AIEF), 1 Haemorrhagic Shock & Encephalopathy (HSE) syndrome and 1 Acute Haemorrhagic Leukoencephalopathy (AHL). Treatments included: systemic steroids in 4 cases, 1 had intravenous immunoglobulin, and 3 cases received both. None received plasma exchange. Influenza vaccination was indicated in eight cases, but none had received it. Conclusion: This paediatric and adult UK cohort identified a severity of influenza related neurological manifestation not reported previously. Cases were more common in children, particularly those with underlying neurological conditions. Encephalopathy syndromes such as ANE, AIEF, HSE and AHL were seen more frequently in children and were associated with a worse outcome. Acute movement disorders and Guillain–Barré syndrome were identified more commonly in adults. Influenza related encephalopathy may be more common in those with abnormal genetically determined host inflammatory responses, but the virus itself is rarely detected in the CSF. Influenza should be considered a cause of acute neurological syndromes in the winter months, especially in children with unexplained encephalopathy. Encephalopathy may be more common with the H1N1 strain. Importantly none of the cases had been vaccinated although many had indications for this.